(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
Red blood cells (RBCs) are very important due to their role of oxygen transport from lungs. As the malaria parasite grows in the malaria-infected red blood cells (IRBCs), the properties of the cells change. In the present work, the oxygen uptake by RBCs and IRBCs at the pulmonary capillaries is simulated using a numerical technique based on the two-dimensional immersed interface method. The results for the oxygen uptake by a stationary single RBC have fair agreements with the previously reported results. The numerical results show that the malaria infection could significantly cause deterioration on the oxygen uptake by red blood cells. The results also suggest that the oxygen uptake by individual stationary RBC/IRBC would not be significantly affected by the neighboring cells provided the separation distance is about the dimension of the cell. Furthermore, it appears that the oxygen uptake by both RBCs and IRBCs is dominated by mass diffusion over the convection although the Peclet number is of the order of unity.